Biaya Marginal dalam Penerapan Matematika Ekonomi - Afiyanti, Yunita; Ridhoilahi, Iftitah; Nur Azizah, Fajrina; Mardyah Nur Afifah, Ainul; Kustiawati, Dedek (Rifa'Institute, 2022)
In general, when building a business or business, the main goal is to get the maximum profit. However, besides that, it also uses capital, sacrifices the smallest possible production costs while maintaining the survival and development of the business. Therefore it is necessary to have a good and structured work plan so that the desired goals can be achieved effectively and efficiently without causing high risks. This study aims to determine the marginal cost as an application of economic mathematics using the literature study method. In this method, researchers examine books and journals related to marginal costs in economic mathematics. The marginal cost of the application of the limit function, the marginal cost is the change in total cost (Q) that occurs due to an increase in production of 1 unit or item. The result of this study is that the limit concept is useful in economics regarding change and the instantaneous rate of change can be used to determine marginal cost. The concept of the marginal is paying attention to the total value or quantity associated with very small changes in the variables that affect it. Marginal cost is the rate of change of total cost due to the addition of one unit of production of goods.